My name is Dominga: story of a terminally-ill woman - Esperanza Begoña García Navarro; Rosa Pérez Espina; Sonia García Navarro (Universidad de Alicante, 2012)
The care of the oncological patient has been and continues being subject of many studies. This story aims to give expression to the needs these patients perceive as real during the process of their illness, regardless of their prognosis. In the development of the disease, the fact of being a woman arises role conflicts within the family and above all in the woman herself, causing a mental duality of guiltiness for her situation and perhaps fatal ending; besides that is the body image and female identity disorder, social and family pressure, and trying to keep up the appearances as if nothing was happening whilst life slips away.